2018
DOI: 10.15171/hpp.2018.31
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette and hookah smoking and their relationship with self-esteem and communication skills among high school students

Abstract: Background: Tobacco smoking is one of the most important public health problems that may be prevented. There is limited information about its relationship with communication skills. Findings on the relationships between self-esteem and cigarette/hookah smoking are inconsistent. The aim of this study was to investigate the relationships between cigarette and hookah smoking,self-esteem and communication skills among a representative sample of high school students. Methods: In this cross-sectional study, a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
3
11
0
1
Order By: Relevance
“…It should be noted that cigarette smoking, hookah use and illicit drug use were related to each other in this study, so that being in advanced level increased the likelihood of being in advanced stage of other ones. These results are in concordance with results of previous studies in Iran (14,17,18,20,21).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It should be noted that cigarette smoking, hookah use and illicit drug use were related to each other in this study, so that being in advanced level increased the likelihood of being in advanced stage of other ones. These results are in concordance with results of previous studies in Iran (14,17,18,20,21).…”
Section: Discussionsupporting
confidence: 93%
“…According to the reports of WHO, the prevalence of tobacco smok- ing among Iranian adolescents, American adolescents, and England adolescents is about 5.9%, 13.4%, and 7%, respectively (11). On the other hand, a previous study in Iran estimated that the prevalence of cigarette experimenter or regular smoking and hookah smoking in Iranian high school students is 18.4% and 38.2%, respectively (14). An-other study from Iran has reported the prevalence of illegal drugs use and cigarette smoking among high school students was 19.2% and 24%, respectively (18).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study showed that about 8.4% of male and 3.3% female used waterpipe in the past 30 days. The result is nearly similar to previous studies on waterpipe use among high school students in the United States and Iran [24,25]. However, the prevalence was considerably higher than the prior study among the older group in Indonesia [18].…”
Section: Discussionsupporting
confidence: 87%
“…Besides, people could give never-ending support to find the best way to solve the smokers' problems to encourage them not to smoke any longer for the search for a solution. Research brought up by Anbarlouei et al (2018) had shown that self-esteem had a significant correlation upon the smoking phase, which means that every improvement on the self-esteem value would degrade the probability value of higher growth on smoking behavior (5%). Another result of previous research also reinforced the correlation between self-esteem and smoking, especially in adolescent scope.…”
Section: Resultsmentioning
confidence: 99%